Optimization of the Estimation Error of Linear Functionals on the Solutions of Hyperbolic Equations - Rusnak, Mykola (Chernivtsi National University, 2024)
In this paper we are continue to study the problems of minimax estimation linear functional under solutions systems of equations with partial derivations. New systems and new observe operators are considerate. New results are obtained in case unknown functions belong to Hilbert spaces with special metrics.
Keywords: minimax, estimation, error